STATISTICAL PROCESSING OF TECHNICAL CHARACTERISTICS OF VIBRATING PLATE COMPACTORS - I. S. Tyuremnov; D. V. Fedorova (Вестник СибАДИ)
Introduction. Currently, manufacturers of vibrating plate compactors practically do not give recommendations on the choice of model and justification of the equipment operating modes when compacting the soil in specific process conditions. This is partially due to the lack of a methodology for determining the results of soil compaction with vibrating plate compactors. One of the development stages of such technique should be the analysis of the technical characteristics of vibrating plate compactors, which could reflect experience in the production and operation of the equipment. Materials and methods. The authors conduct statistical processing of technical characteristics of vibrating plate compactors in STATISTICA 10 based on 65 models of various manufacturers from Russia and other countries.Discussion and conclusions. The authors demonstrate that the operating modes of vibrating plate compactors are between the operating modes of vibrating rollers and self-propelled vibrating plate compactors. To note, relative driving forces are in a similar range as the working range of self-propelled vibrating plate compactors, and their vibration frequencies are in a similar range as the working range of vibrating rollers. Moreover, low values of the determination coefficient for oscillation frequency and relative forcing force depending on the mass of the equipment also indicate the lack of consensus among manufacturers about the required characteristics of vibrating plate compactors and an assessment of their technological capabilities.Due to a significant excess of driving force of vibrating plate compactors over their weight, the base of the plate should come into partial uplift from soil, and that should be taken into account while the mathematical model of interaction development between vibrating plate compactors and soil. Practical implications. The results of the analysis reveal the peculiarities of the vibrating plate conductors’ interaction with the compacted soil and also clarify the requirements for the future mathematical model. The resulting regression dependencies of driving force and oscillation frequency, as well as the base dimensions of the vibrating plate compactors, the weight of the excavator and the required oil consumption should be taken into account when developing a methodology for determining the results of soil compaction with mounted technological excavator plates. Therefore, the obtained results could also be used by manufacturers in the design and modernization of the vibrating plate compactors’ structures.